Two new species of Thyridosmylus Kruger (Neuroptera: Osmylidae) from China - Wang, Yongjie; Du, Xiangge; Liu, Zhiqi (Zootaxa, 2008)
The genus Thyridosmylus Krüger (Neuroptera: Osmylidae) belongs to the subfamily Spilosmylinae based on the type species Osmylus langii Mclachlan 1870 (Krüger 1913). The genus has 19 species mainly distributed in Asia, especially in China where there are 14 species: Thyridosmylus polyacanthus sp. nov., Thyridosmylus trimaculatus sp. nov., Thyridosmylus minoroides Yang, 1987, Thyridosmylus laetus Yang, 1988, Thyridosmylus pulchrus Yang, 1988, Thyridosmylus medoganus Yang, 1988, Thyridosmylus similaminor Yang, 1992, Thyridosmylus trifasciatus Yang, 1993, Thyridosmylus triypsiloneurus Yang, 1995, Thyridosmylus maolanus Yang, 1993, Thyridosmylus qianus Yang, 1993, Thyridosmylus fuscus Yang, 1999, Thyridosmylus vulgatus Yang, 1999 and Thyridomsylus pallidius Yang, 2002. Three species are described from India (Thyridosmylus langii (McLachlan 1870), Thyridosmylus perspicillaris (Gerstaecker, 1885), Thyridosmylus pustulatus Kimmis 1942) while another two species are known from Madagascar (Thyridosmylus marmoratus Fraser, 1955 and Thyridosmylus punctulatus (Navás, 1933)). Gerstaecker (1885) described one subspecies Thyridosmylus perspicillaris perspicillaris Gerstaecker and Kimmins (1942) erected three additional subspecies, Thyridosmylus langii angustus Kimmins, 1942, Thyridosmylus perspicillaris fenestratus Kimmins, 1942, Thyridosmylus perspicillaris minor Kimmins, 1942. However due to rampant variation in colouration and venation, the valid status of these subspecies is doubted and they are provisionally treated as synonyms herein. Thyridosmylus is characterised by fuscous and maculate forewings and largely hyaline hind wings, moderately sized and usually ochreous body, costal cross-veins simple and radial field with numerous cross veins (not including gradates). In the male genitalia, the anal plate generally elevates into a fingerlike process on the dorsal margin, and parameres are commonly arcuate in lateral view. Female genitalia usually have a broad anal plate, while the gonapophysis lateralis is finger-like or coniform in lateral view. In this paper, two new species are described from China. Terminology follows Tjeder (1957) and New (1986). All the type specimens are deposited in the Entomological Museum of China Agricultural University (CAU), Beijing.